Provider medicaid fraud: A note on white-coat crime - Cullen, Francis T. (American journal of criminal justice, 1984)
To date, relatively few empirical studies have been conducted of provider medicaid fraud or, more generally, of “white-coat crime”--offenses by health professionals. Based on data accumulated by a quality control unit on the duplicate billings for a single service by New York State providers, the present research attempts to help fill this void by assessing the prevalence of medicaid fraud. Two conclusions are suggested by the data. First, unlike other realms of upperworld criminality, provider fraud does not appear to be pervasive. Second, provider occupations with more of a business orientation appear to have a greater involvement in fraudulent activities than groups that are more fully professionalized.